Systematic Violence Monitoring to Reduce Underreporting and to Better Inform Workplace Violence Prevention Among Health Care Workers: Before-and-After Prospective Study - Giovanni Veronesi; Marco Mario Ferrario; Emanuele Maria Giusti; Rossana Borchini; Lisa Cimmino; Monica Ghelli; Alberto Banfi; Alessandro Luoni; Benedetta Persechino; Cristina Di Tecco; Matteo Ronchetti; Francesco Gianfagna; et al. (JMIR Publications, 2023)
BackgroundMonitoring workplace violence (WPV) against health care workers (HCWs) through incident reporting is crucial to drive prevention, but the actual implementation is spotty and experiences underreporting. ObjectiveThis study aims to introduce a systematic WPV surveillance in 2 public referral hospitals in Italy and assess underreporting, WPV annual rates, and attributes "before" (2016-2020) and "after" its implementation (November 2021 to 2022). MethodsDuring 2016-2020, incident reporting was based on procedures and data collection forms that were neither standardized between hospitals nor specific for aggressions. We planned and implemented a standardized WPV surveillance based on (1) an incident report form for immediate and systematic event notification, adopting international standards for violence definitions; (2) second-level root cause analysis with a dedicated psychologist, assessing violence determinants and impacts and offering psychological counseling; (3) a web-based platform for centralized data collection; and (4) periodic training for workforce coordinators and newly hired workers. We used data from incident reports to estimate underreporting, defined as an observed-to-expected (from literature and the "before" period) WPV ratio less than 1, and the 12-month WPV rates (per 100 HCWs) in the "before" and "after" periods. During the latter period, we separately estimated WPV rates for first and recurrent events. ResultsIn the "before" period, the yearly observed-to-expected ratios were consistently below 1 and as low as 0.27, suggesting substantial violence underreporting of up to 73%. WPV annual rates declined in 1 hospital (from 1.92 in 2016 to 0.57 in 2020) and rose in the other (from 0.52 to 1.0), with the divergence being attributable to trends in underreporting. Available data were poorly informative to identify at-risk HCW subgroups. In the "after" period, the observed-to-expected ratio rose to 1.14 compared to literature and 1.91 compared to the "before" period, consistently in both hospitals. The 12-month WPV rate was 2.08 (95% CI 1.79-2.42; 1.52 and 2.35 in the 2 hospitals); one-fifth (0.41/2.08, 19.7%) was due to recurrences. Among HCWs, the youngest group (3.79; P<.001), nurses (3.19; P<.001), and male HCWs (2.62; P=.008) reported the highest rates. Emergency departments and psychiatric wards were the 2 areas at increased risk. Physical assaults were more likely in male than female HWCs (45/67, 67.2% vs 62/130, 47.7%; P=.01), but the latter experienced more mental health consequences (46/130, 35.4% vs 13/67, 19.4%; P=.02). Overall, 40.8% (53/130) of female HWCs recognized sociocultural (eg, linguistic or cultural) barriers as contributing factors for the aggression, and 30.8% (40/130) of WPV against female HCWs involved visitors as perpetrators. ConclusionsA systematic WPV surveillance reduced underreporting. The identification of high-risk workers and characterization of violence patterns and attributes can better inform priorities and contents of preventive policies. Our evaluation provides useful information for the large-scale implementation of standardized WPV-monitoring programs.